Main Pedagogical Technologies of Selection and Orientation used in Children for Sports Reserve - Karimov Davron Akulovich (International Journal on Integrated Education, 2022)
This article discusses pedagogical technologies of training sports reserve in various sports that contribute to the improvement of the athletes training system at the initial stage of preparation for a professional sport. The purpose of the research is the development and scientific justification of the pedagogical technologies for training reserve in various sports. The relevance of the article is due to the fact that great importance has been attributed recently to the improvement of the training system for the sports reserve, which ensures the replenishment of the national teams.